ChemInform Abstract: Aza‐Michael Access to Fluoroalkylidene Analogues of Biomolecules. Issue 1 (7th January 2014) - Prunier, Anais; Calata, Charlene; Legros, Julien; Maddaluno, Jacques; Pfund, Emmanuel; Lequeux, Thierry
Abstract A direct access for the preparation of fluoroallylamines via an aza‐Michael reaction followed by a modified Julia reaction is presented.